KARAKTERISTIK BRIKET ARANG CAMPURAN ARANG AKASIA DAUN KECIL (Acacia auliculiformis) DAN ARANG ALABAN (Vitex pubescens vhal) - Fadillah Yusma Sugiyati; Budi Sutiya; Yuniarti - (Universitas Lambung Mangkurat, 2021)
Petroleum is an energy that cannot be renewed, but in everyday life, fuel oil is still the main choice so that it will recult in depletion of petroleum reserves. This study aims to analyze the quality of the charcoal briquette mixture of small leaf acacia wood charcoal whit a mixture of alaban wood charcoal. Parameters tested based on (ASTM D 5142 – 02). Charcoal briquette quality result obtained using Indonesian state standards (Indonesian National Standards – SNI). The results of research from small leaf acacia charcoal and alaban charcoal resulted in the average value of moisture content testing, density testing, ansh content testing, flight substance testing bound carbon content testing and calorific value testing. Testing of moisture content, density, ash content and calorific value met Indonesian standards, while testing for aerobic substances and bound carbon content did not meet Indonesian standards. The best quality charcoal briquettes that meet all the criteria of the Indonesian state standards (Indonesian National Standards – SNI) in treatment E (75% alaban charcoal and 25% small leaf acacia charcoal). The results obtained indicate that each treatment differences in the composition of charcoal powder have a significant effect on each parameter such as moisture content, density, ash content, flying matter, carbon content and calorific value.Keywords: Energy; Brike; Acacia; Alaban